Treatment of urogenital mixed infection in women of reproductive age: current state of problem - O I Letyaeva; O A Hisinger (IP Berlin A.V., 2014)
An open, randomized clinical and immunological and microbiological study of 102 women of reproductive age with inflammatory diseases of the genitourinary system associated with opportunistic microorganisms has been held. It has shown that the presence of genital tract Mycoplasma hominis, Ureaplasma urealyticum, fungi of the genus Candida is accompanied by impaired innate immune factors, changes in the qualitative and quantitative composition of the resident microflora. Application in the complex therapy of the drug in the form of polyoxidonium suppositories at a dose of 6 mg daily for 10 days promotes a more rapid resolution of symptoms of inflammation, eliminating the imbalance in the local immune status, and thus leading to restoration of colonization resistance compared to baseline therapy.